2021
DOI: 10.1111/aogs.14224
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of human epididymis protein 4 (HE4) for discriminating between benign and malignant pelvic masses: a systematic review and meta‐analysis

Abstract: Introduction: Many women with benign pelvic masses, suspected of ovarian cancer, are unnecessarily referred for treatment at specialized centers. There is an unmet clinical need to improve diagnostic assessment in these patients. Our objective was to obtain summary estimates of the accuracy of human epididymis protein (HE4) for diagnosing ovarian cancer and to compare the performance of HE4 with that of cancer antigen 125 (CA125). Material and methods:We searched PubMed, Ovid and Scopus using search terms for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
(116 reference statements)
2
14
0
Order By: Relevance
“…Previous epidemiological studies have investigated the diagnostic role of HE4 in some diseases, such as OC ( 13 , 14 ), lung cancer (LC) ( 15 ), renal fibrosis ( 16 ), breast cancer ( 17 ), and endometrial carcinoma (EC) ( 18 ). For example, the results of a meta-analysis showed that HE4 had higher specificity (0.84 vs. 0.57) and similar sensitivity (0.79 vs. 0.81) than CA125 for differentiating malignant from benign pelvic mass disease ( 19 ), similar findings could be observed in those meta-analyses ( 7 , 20 , 21 ). However, a meta-analysis demonstrated that HE4 was no better than CA125 for OC prediction ( 22 ).…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Previous epidemiological studies have investigated the diagnostic role of HE4 in some diseases, such as OC ( 13 , 14 ), lung cancer (LC) ( 15 ), renal fibrosis ( 16 ), breast cancer ( 17 ), and endometrial carcinoma (EC) ( 18 ). For example, the results of a meta-analysis showed that HE4 had higher specificity (0.84 vs. 0.57) and similar sensitivity (0.79 vs. 0.81) than CA125 for differentiating malignant from benign pelvic mass disease ( 19 ), similar findings could be observed in those meta-analyses ( 7 , 20 , 21 ). However, a meta-analysis demonstrated that HE4 was no better than CA125 for OC prediction ( 22 ).…”
Section: Introductionsupporting
confidence: 57%
“…Subsequently, a further 34 articles were excluded for the following reasons: 13 presented insufficient data, 6 did not conduct meta-analysis, 4 explored outcomes that we were not interested in, 4 published not in English, the full text of 3 articles were not available, 2 published duplicated reports, 1 explored exposure that we were not interested in, and 1 conducted less than three original studies. Ultimately, 20 studies ( 7 , 8 , 15 , 19 22 , 42 54 ) were eligible to be included in the main analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca125, a mucin, is considered by the FDA to be the gold standard for the management of the OC, although it showed low sensitivity in the early stages of the disease. Increasing levels of this biomarker have been also found in other physiological or pathological conditions, such as menstruation, pregnancy, endometriosis and inflammatory diseases of the peritoneum [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating CA125 levels increase with tumor burden, but—conversely—they do not exceed the usual cutoff of 35 U/mL at 50% of early OC [ 15 ]. The sensitivity of CA125 has been reported at 0.78–0.86, the specificity at 0.57–0.82, the positive predictive value (PPV) at 0.50–0.68 and the negative predictive value (NPV) at 0.9–0.95 [ 11 , 12 , 16 , 17 , 18 , 19 ]. Amongst a further 200 investigated biomarkers, the cancer antigens CA 72.4, CA 15.3, CA 19.9 and HE4 have been considered the most informative for the evaluation of adnexal mass [ 4 , 13 , 20 ].…”
Section: Introductionmentioning
confidence: 99%